ABA-Adaptive Bidirectional A Algorithm for Aerial Robot Path Planning - Wang, Pengkai; Mutahira, Husna; Kim, Jonghoek; Muhammad, Mannan Saeed (IEEE access, 2023)
The extensive use of robots has led to the rapid development of related technologies, such as automatic guidance and the use of drones in various applications. The challenge in path planning for robots involves finding collision-free paths that satisfy physical and kinematic constraints. The A* algorithm is commonly used for path planning in mobile robot, but its efficiency is reduced in large 3D environments due to high computational demands. This study introduces an improved version of the A* algorithm, called the Adaptive Bidirectional A* algorithm, specifically designed for path planning in 3D environments. The algorithm adapts to 3D environment variables and utilizes bidirectional search to find the optimal path. Compared to the original A* algorithm, the new algorithm significantly reduces planning time, up to 91.2%. The algorithm is applied to quadcopter path planning, and the simulation results demonstrate its superior performance. Furthermore, theoretical analysis validates the efficiency of the algorithm. Overall, the proposed ABA* algorithm shows great potential for real-world applications that require proposed path planning in 3D environments with limited computational resources.